Contracting still matters! Or: how to design a letter of intent - Evelyn Korn; Stephan Meisenzahl (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
Any cooperation that profits from relation-specific investments suffers from the well-known hold-up problem. If investments are not enforceable by an outside authority, the gains fall prey to individual opportunism caused by a free-rider problem. If, in addition, individual investments exhibit positive cross effects, Che and Hausch (1999) provide a negative result and show that contracts cannot overcome the hold up due to a lack of verifiable commitment. This paper develops a mechanism that provides such a commitment device: (1) It introduces an acknowledgement game that procures reliable. (2) It embeds the original contracting problem into two institutional designs - a market based one and a private design - that support enforcement. These two devices reestablish efficient investments as enforceable results of a contract.
Keywords: 330